Extension Methodologies For Transfer Of Agricultural Technology - Somani, L.L.; Somani, L.L. (Udaipur Agrotech, 2012)
this book brings together highly rich information on extension methodologies and communication technologies
chain network star network circle network orientation feedback
Keywords: circle network ,orientation ,feedback